The Charter and Code of the Ordinances of Yazoo City 174, ch. 20, § 299 (1908). - (:unkn) unknown (General Publisher, 1906)
Any student or pupil in any public school of this city, who shall carry into such school any weapon of the kind mentioned or described in section 293, concealed, in whole or in part, or any professor, teacher, or instructor in such school who shall knowingly suffer or permit any such weapon to be carried into such school, concealed, as aforesaid, shall be guilty of a misdemeanor, and, on conviction thereof in the city court, shall be punished as provided in section 293.
--
Keywords: SENSITIVE PLACES